A The Improvement of Religious Education Learning Outcomes Through Application of Discovery Learning in Elementary Schools: - - Agustinus Daga; Mariana Malo; Mikael Sene (Universitas Djuanda Bogor, 2025)
Religious education plays a crucial role in shaping the Pancasila character of elementary school students. It contributes to the internalization of the noble values of Pancasila. The purpose of this study is to improve the learning outcomes of Catholic Religious Education for elementary school students through the use of discovery learning. The subjects of this research are the fourth-grade students of SDN Mananga Aba. The research method used is Classroom Action Research, which includes planning, implementation, observation, and reflection. Data collection was done using a test technique, consisting of 10 multiple-choice questions. The data analysis is descriptive covering student completion, class completion, and the analysis of teacher and student activity observations. The results of this study show that, in cycle I, students achieved a score of 65, which increased to 85 in cycle II. The teacher activity observation score in cycle II was 96, while in Cycle I it was 56. The student activity observation score in cycle II was 96, while the cycle I score was 63. The teacher and student scores in cycle II have reached the Good category. This research concludes that the implementation of discovery learning can improve the learning outcomes of fourth-grade students at SDN Mananga Aba. This finding implies an enhancement in teachers' comprehension and abilities in utilizing discovery learning to further improve student achievement.